If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 14 = -40 + -3x Reorder the terms: 14 + 6x = -40 + -3x Solving 14 + 6x = -40 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 14 + 6x + 3x = -40 + -3x + 3x Combine like terms: 6x + 3x = 9x 14 + 9x = -40 + -3x + 3x Combine like terms: -3x + 3x = 0 14 + 9x = -40 + 0 14 + 9x = -40 Add '-14' to each side of the equation. 14 + -14 + 9x = -40 + -14 Combine like terms: 14 + -14 = 0 0 + 9x = -40 + -14 9x = -40 + -14 Combine like terms: -40 + -14 = -54 9x = -54 Divide each side by '9'. x = -6 Simplifying x = -6
| 3x+5y=2.37 | | 2x+3(4+2x)=8 | | 3z-8=z-10 | | 29+v=13 | | -3m+6=12 | | 8+32-36-(-7)= | | f(x)=3x^2+4x-4 | | -64=-16x | | -x+13=x-13 | | 8+2(16-36)-(-7)= | | 6x/-2x/21=25/21 | | -5+-7-(-4)= | | 2+y=-7+2 | | x+4=105x-104 | | -4a=-28 | | u^2-12u+17=0 | | -5x+3(6x+-16)=191 | | -4y+42=-6+2y | | 0.4x-0.7+0.3x=7 | | 4(6.25)+3x=34.60 | | 6-5-3(2)=8 | | m^4+7m^2=0 | | 3u^2-48=0 | | y+10=20-y | | x+5/3= | | 2-h=-32 | | 10x^7/5x^2/7 | | f=-48n+22000 | | 5y-9=7+9y | | Y=-4.2+3.6X | | 15x+32=7x-28 | | 13-8x=-7-3x |